METHODOLOGY FOR DEVELOPING INDUCTIVE AND DEDUCTIVE THINKING THROUGH A CLUSTER APPROACH IN HIGHER EDUCATION - Shermatova, Saxobaxon (UZBEKISTAN — 2030: PROSPECTS FOR INNOVATION, SCIENCE AND EDUCATION, 2025)
This article analyzes the theoretical and practical aspects of developing students’ inductive and deductive thinking in the higher education system based on a cluster approach. A methodology for forming students’ logical, analytical, and creative thinking skills through the cluster education model has been developed. Additionally, the effectiveness of the cluster approach has been experimentally substantiated.